Response of Walkwater Growth to Giving of Fishing Waste-Based POC to Inceptisol - Amin Mbusango; Anne Nurbaity; Ratna Ningsi; Indra Permana; Kati Syamsudin Kadang Tola (Jurnal Biologi Tropis, 2023)
Agricultural land that has low nutrient status can inhibit plant growth, so it is necessary to add nutrients to the soil without causing enviromental damage.  The research was aimed to observed growth response of kangkong on combination NPK and level doses of POC fishery wasted on Inceptisol soil.The research was aimed to observed growth response of kangkong on combination NPK and level doses of POC fishery wasted on Inceptisol soil. This research used a split plot design, the main plot consists of: V0 (without used NPK) and V1 (used NPK).Data analysis using variance with the DSAASTAT application. If the variance shows a significant effect, then it is continued with Duncan’s multiple range test (UJBD) at the 95% level of confidence. The results showed  application of POC based on fishery wasted added with NPK can provide a good responses to the heigh of the kangkong plant, the number of kangkong leaves, the fresh weight of kangkong roots and leaves, the dry weight of kangkong roots and leaves and the increase in the number of AMF spores in the rhizosphere of kangkong plants. The best responsed influence of the growth of kangkong plants was combination of NPK and 75% POC doses based on fishery wasted. Utilization of processed fishery wasted as POC can be alternative as an enviromentally friendly organic fertilizer in increasing the yield of kangkong plants.